2008
DOI: 10.1186/1755-8166-1-21
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of trisomy 21 Down syndrome

Abstract: BackgroundDown syndrome, characterized by an extra chromosome 21 is the most common genetic cause for congenital malformations and learning disability. It is well known that the extra chromosome 21 most often originates from the mother, the incidence increases with maternal age, there may be aberrant maternal chromosome 21 recombination and there is a higher recurrence in young women. In spite of intensive efforts to understand the underlying reason(s) for these characteristics, the origin still remains unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
130
6
4

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(142 citation statements)
references
References 37 publications
2
130
6
4
Order By: Relevance
“…In fact, a previous work that analysed oocytes from eight euploid fetuses described the presence of aneuploid 21 oogonia, and the authors considered mosaicism in the ovaries as a normal situation in normal female fetuses. 20 Mitotic chromosome segregation errors found in oocytes could have two different explanations. On the one hand, they could have been produced in the first mitotic divisions of the embryo, where the aneuploid cells were later recruited in certain tissues, in this case the ovaries.…”
Section: Oocyte Aneuploidymentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, a previous work that analysed oocytes from eight euploid fetuses described the presence of aneuploid 21 oogonia, and the authors considered mosaicism in the ovaries as a normal situation in normal female fetuses. 20 Mitotic chromosome segregation errors found in oocytes could have two different explanations. On the one hand, they could have been produced in the first mitotic divisions of the embryo, where the aneuploid cells were later recruited in certain tissues, in this case the ovaries.…”
Section: Oocyte Aneuploidymentioning
confidence: 99%
“…This is the reason why there is an accumulation of these oocytes in the ovarian reserves of older women. 20,33 To shed light on the effect of hormonal stimulation in relation to natural cycles and, later, conclude whether or not the protocols applied favour aneuploid oocyte recruitment and maturation instead of euploid ones, as has been suggested before, 34 more research should be performed.…”
Section: Oocyte Aneuploidymentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently it has been suggested that the maternal age effect is a multifactorial trait, and may be influenced by environmental factors ( 8,9 ). Another intriguing possibility it that normal women may be trisomy 21 ovarian mosaics ( [11][12][13] with the potential for oocytes containing three chromosomes 21 accumulating during maturation and when reaching MI undergoing obligatory secondary non-disjunction at AI.…”
Section: Linkage Analysis Of Trisomy 21mentioning
confidence: 99%